Use of Quantitative Ultrasound to Measure Acoustic Properties of Human Skin - PIOTRZKOWSKA, Hanna; LITNIEWSKI, Jerzy; LEWANDOWSKI, Marcin; SZYMAŃSKA, Elżbieta; NOWICKI, Andrzej (Archives of Acoustics, 2009)
The scattering of ultrasonic waves depends on the size, shape, acoustical properties and concentration of scatterers in the tissue. The spectrum of the ultrasonic backscatter can be used to characterize non-invasively the structural and mechanical properties of tissue. We intend to apply the custom-designed high-frequency ultrasonic scanner for the skin and cutaneous lesions characterization by evaluating their attenuating and scattering properties. In this pilot study, we have explored the possibility of extracting the human skin backscattering coefficient (BC) from the ultrasonic B-scans obtained in vivo at 20-30MHz. The measured BC values of normal skin (dermis) agree well with the published data. We have found also that the spatial resolution of the BC determination using our scanner is sufficient (aprox. 1mm2) to characterize small skin lesions and assess their penetration depth.